Reporting and statistics of pilotage incidents within the Swedish Maritime Administration - An analysis of incidents during pilotage from 2004 to 2014 - sölver, andreas; johansson, linus (My University, 2015)
The Swedish Maritime Administration (SMA) asked for assistance in finding out whether incident reporting patterns could be made visible within their field of pilotage. Since regulations - both international and national - governs when and how a maritime incident report should be written certain aspects of the reports are important to consider. Research regarding reporting among pilots showed to be difficult to find, why studies examining incidents and incident reporting in general terms have been referred to. The overall question of this study is whether or not statistical patterns can be traced from the reports received from the SMA. This question was further deepened looking for specifics in the material, such as degree of seriousness and influence of weather condition. The material consisted of 94 reports received by the SMA during the fall of 2014. The reports dated from year 2004 to 2014 and was analysed in part using of a method called TRACEr. Here, information was sorted into different categories regarding for instance type of incident and location. This information was then presented in relevant diagrams for each of the investigated categories. Results showed that bulk carriers and tankers were the most frequently appearing ship types in the statistics and that “Machinery damage” followed by “Contact” (with fixed or floating objects) are the most common causes of an event. Most of the incidents were of less serious nature while merely about 10 percent were categorised as serious and very serious casualties. Statistics on weather show that in almost two thirds of the incidents there was no significant weather effect.
Keywords: Transport; Annan teknik; Transport; Other Engineering and Technologies